Occupational Health and Safety Program in Efforts to Fulfill Nurses' Rights in Isolation Rooms During The Covid-19 Pandemic (Case Study at Charitas Hospital Palembang) - Rusli, Noer Triyanto; Dewi, Trihoni Nalesti; Hartini, MC Inge (Soepra Jurnal Hukum Kesehatan, 2023)
The hospital as a health service institution for the community is a place of work that has a high risk of safety and health. The fulfillment of the right to Occupational Safety and Health for health workers is very necessary, because health workers are of course vulnerable to occupational safety and health hazards. Charitas Hospital as one of the COVID-19 referral hospitals in Palembang City has a very high potential danger of COVID-19 transmissionThis study aims to find out how the regulation of Charitas Hospital can guarantee the fulfillment of Occupational Health and Safety rights. The approach method used in this research is the sociological juridical method.Based on the Legislation which discusses Human Rights, Employment, and Health there are no regulations that overlap, redundant, or there is a void in the legislation governing the rights of Occupational Safety and Health of nurses in Isolation Rooms during a pandemic. COVID-19. In the event of a vacancy in laws and regulations due to the COVID-19 pandemic, the Government may issue policy regulations (beleidsregel) such as Presidential Instructions, Circulars, Guidelines, Technical Standards, and Protocols and Charitas Hospital Palembang to make internal policies (SOPs, Instructions for Technical, Technical Standards) and adding Nursing Staff Bylaws related to handling arrangements during a pandemic so that the Hospital is ready if at any time a similar incident occurs.